The digestive adaptation of flying vertebrates: High intestinal paracellular absorption compensates for smaller guts - Caviedes-Vidal, Enrique (National Academy of Sciences, 2007)
Anecdotal evidence suggests that birds have smaller intestines than mammals. In the present analysis, we show that small birds and bats have significantly shorter small intestines and less small intestine nominal (smooth bore tube) surface area than similarly sized nonflying mammals. The corresponding >50% reduction in intestinal volume and hence mass of digesta carried is advantageous because the energetic costs of flight increase with load carried. But, a central dilemma is how birds and bats satisfy relatively high energy needs with less absorptive surface area. Here, we further show that an enhanced paracellular pathway for intestinal absorption of water-soluble nutrients such as glucose and amino acids may compensate for reduced small intestines in volant vertebrates. The evidence is that l-rhamnose and other similarly sized, metabolically inert, nonactively transported monosaccharides are absorbed significantly more in small birds and bats than in nonflying mammals. To broaden our comparison and test the veracity of our finding we surveyed the literature for other similar studies of paracellular absorption. The patterns found in our focal species held up when we included other species surveyed in our analysis. Significantly greater amplification of digestive surface area by villi in small birds, also uncovered by our analysis, may provide one mechanistic explanation for the observation of higher paracellular absorption relative to nonflying mammals. It appears that reduced intestinal size and relatively enhanced intestinal paracellular absorption can be added to the suite of adaptations that have evolved in actively flying vertebrates.